Comparative assessment of metabolic processes in children living in the areas affected by the Сhernobyl nuclear power plant accident (Environment & Health, 2017)
Objective: We performed a comparative assessment of metabolic processes in the children living for a long time in Polissia and Ivankiv districts of Kyiv oblast, at the territories contaminated with radioactive elements as a result of the accident at the Chornobyl NPP.Materials and methods: We determined a content of 137Cs radionuclides, a content of thyrotropic pituitary hormones, triiodothyronine, thyroxin, homocysteine, vitamins B9, B12 in the blood of the adolescents, and a state of folate metabolism genetic system as well.The immunochemical and mathematical-and-statistical methods were applied.Results: The percentage of the children in the age group under study with 137Cs concentration in the organism over 5 Bq/kg of body weight was 34.1 % in Polissia district and was significantly higher (p
Keywords: homocysteine; folate metabolism; thyroid and pituitary hormones; folic acid; vitamin B12; adolescents; radiation-contaminated areas